Knowledge about Computer Vision Syndrome among Bank Workers in Gondar City, Northwest Ethiopia - Getasew Alemu Mersha; Mohammed Seid Hussen; Gizachew Tilahun Belete; Melkamu Temeselew Tegene (Hindawi-Wiley, 2020)
Background. Globally, computer vision syndrome is the most common eye problem which is associated with prolonged exposure to a computer. It has a great socioeconomic impact on the users due to its effect on job performance. Recently, many people in the world, including our country Ethiopia, especially bank workers, are spending most of their time in front of a computer screen to facilitate their work. Since it is assumed that knowledge is pertinent to prevent computer vision syndrome, this study was aimed at assessing the understanding of bank workers towards computer vision syndrome. Methods. An institution-based cross-sectional study was conducted on 248 bank workers. The study participants were selected by using a simple random sampling technique. A self-administered questionnaire was used to collect the data from the bank workers. The data was entered and analyzed by SPSS version 21 software. Results. A total of 248 bank workers completed the questionnaire fully, which was a response rate of 93.5% (n=234). Among them, 155 (66.20%) were males and the majority of the respondents were in the age group of 20-39 years (223, 95.3%). The study revealed that from 234 respondents, 211 (90.20%) were aware of computer vision syndrome, while 26.9% of them had a good knowledge about the disorder. Majority of the respondents (40, 17.1%) cited mass media as a source of information. Conclusion. Even though the majority of computer-using bank workers heard of computer vision syndrome, it was recognized that only a small portion of the participants had good knowledge.